Multicentric, observational, longitudinal study for the evaluation of nutritional management implications in newly diagnosed Italian cancer patients: the Italian Registry of Malnutrition in Oncology (IRMO) - Paolo Pedrazzoli; Sandro Pignata; Patrizia Serra; Francesco De Lorenzo; Elisabetta Iannelli; Toni Ibrahim; Cristina Bosetti; Carmine Pinto; Valentina Da Prat; Riccardo Caccialanza; Vittorina Zagonel; Filippo Montemurro; et al. (BMJ Open)
Background Malnutrition is a frequent problem in oncology and is associated with reduced response to cancer treatments, increased drug-related toxicity, higher rates of clinical complications, reduced quality of life (QoL) and worse prognosis. Guidelines on clinical nutrition in oncology emphasise the usefulness of early assessment of nutritional status for a prompt identification of malnutrition and the implementation of effective interventions, but no real-world clinical data are available on the adequate management of nutritional support in patients with cancer in Italy.Methods and analysis This is an observational, longitudinal, multicentre registry of patients with a new diagnosis of cancer or metastatic disease, candidates for active treatment. They will be identified in at least 15 Italian oncological centres, members of the Alliance Against Cancer Working Group ‘Survivorship Care and Nutritional Support’. At least 1500 patients with cancer are expected to be enrolled each year. Detailed clinical and nutritional data will be collected by oncologists and clinical nutritionists during the visits foreseen in the clinical practice, through an ad hoc developed digital platform (e-Nutracare). The effects of malnutrition and nutritional support—at diagnosis and during follow-up—on overall survival and progression-free survival, as well as on patients’ symptoms and QoL, will be investigated.Ethics and dissemination The study protocol was approved by the Ethics Committee of the Fondazione IRCCS Policlinico San Matteo, Pavia, Italy and from the Ethics Committees of all other participating centres. An informed consent will be obtained from each patient enrolled in the study. Study findings will be disseminated through peer-reviewed journals, conferences and patients with cancer or professional associations. The registry will allow a better monitoring of the nutritional status of patients with cancer, promoting adequate and sustainable nutritional support, with the ultimate goal of improving the care and prognosis of these patients.